The Effect of Project Based Learning Implementation Toward Students’ Motivation and Learning Result at Elementary School - Mukhlis Syahroni; Parji Parji; Muhammad Hanif (International Journal Labs, 2026)
The Merdeka Curriculum emphasizes deep learning, making Project-Based Learning (PjBL) a promising method to enhance students' motivation and learning outcomes. However, at SDN 01 Demangan, diagnostic assessment revealed that only 16.67% of sixth-grade students were in the skilled category, while 72.22% remained in the less skilled category, indicating persistent challenges in motivation and learning achievement. This study aims to analyze the effect of Project-Based Learning implementation on students' motivation and learning outcomes in the Integrated Science (IPAS) subject. Using a quantitative approach with a one-group pretest-posttest design, this research involved 18 sixth-grade students who participated in a PjBL project themed